2004
DOI: 10.1152/ajpheart.01101.2003
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine kinase-1 mediates TNF-α-induced MCP-1 gene expression in endothelial cells: upregulation by oscillatory flow

Abstract: Atherosclerosis is a focal inflammatory disease and preferentially occurs in areas of low fluid shear stress and oscillatory flow, whereas the risk of atherosclerosis is decreased in regions of high fluid shear stress and steady laminar flow. Sphingosine kinase-1 (SphK1) catalyzes the conversion of sphingosine to sphingosine-1 phosphate (S1P), a sphingolipid metabolite that plays important roles in angiogenesis, inflammation, and cell growth. In the present study, we demonstrated that exposure of human aortic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
48
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(54 citation statements)
references
References 42 publications
(47 reference statements)
4
48
0
1
Order By: Relevance
“…This hypothesis is also corroborated by the observed SphKdependency of p38 MAPK activation by TNFa in endothelial cells [19].…”
Section: Discussionsupporting
confidence: 54%
“…This hypothesis is also corroborated by the observed SphKdependency of p38 MAPK activation by TNFa in endothelial cells [19].…”
Section: Discussionsupporting
confidence: 54%
“…These observations suggest that MCP-1 production in macrophages is also controlled by the SK1-S1P pathway. This finding is in agreement with previous reports showing that incubation of human mammary endothelial cells and a neuroblastoma cell line with extracellular S1P increases MCP-1 expression in a time-and concentration-dependent manner (44,45).…”
Section: Discussionsupporting
confidence: 94%
“…Human SPHK1-specific 21-nucleotide siRNA oligo (Dharmacon Research; GAGCUGCAAGGCCUUGCCCdTdT and GGGCAAGGCCUUGCAG CUCdTdT) targets 70 nt downstream of the start codon as described previously (23)(24)(25). These previous studies also showed that the above SPHK1 siRNA specifically inhibits SPHK1 mRNA expression.…”
Section: Transfection Of Sirnamentioning
confidence: 96%